Optimization and effects of process variables on the production and properties of methyl ester biodiesel - Eloka-Eboka, Andrew C.; Igbum, Ogbene Gillian; Inambao, Freddie L. (Journal of Energy in Southern Africa, 2014)
Optimization of the production process in biodiesel production holds huge prospects. A reduced cost option is the optimization of process variables that affect yields and purity of biodiesel, which was achieved in this study. Optimized production and direct effects of process variables on the production and quality of methyl ester biodiesel fuels from the non-edible seed oils of sandbox seed was carried out. Catalyst nature and concentration, alcohol to triglyceride molar ratio, mixing speed, reaction time and temperature were taken into consideration as variables to their individual response on the yields, viscosity and specific gravity of the methyl esters produced. These are specific indispensable properties of biodiesel for use in compression ignition engines. Optimized concentrations were 0.3 to 1.5% w/v and two mole ratios of 3:1 and 6:1. Time of reaction was varied (5mins to 30mins) with temperatures (38oC and 55oC). Also, the effect of methanol in the range of 4:1and 6:1 (molar ratio) was investigated, keeping catalyst type, reaction time and temperatures constant. The effects of KOH and NaOH on the transesterification were investigated with concentration kept constant at 1%. The general response in this study was that at optimized rate of agitation (800rpm), optimized reaction time was as low as 5minutes, 1% catalyst concentration of NaOH was the optimal concentration, and 55oC was the optimal temperature with attendant high yields. However, there are variations with the nature of feedstock as the work further exposed. These high points are particularly of interest to guide against process backdrop.